DUTIES OF A STAFF HUMAN RESOURCE DEVELOPMENT IN HR-REPRESENTATIVE DEPARTMENT AT PT.TELKOM KANDATEL MALANG - ASY’HARI, AKHMAD RIZAL (Jurnal Ilmiah Mahasiswa FIB, 2013)
In developing a company,  every entrepreneur must  be able to manage theiremployee  as  good  as  possible.  Every  entrepreneur  definitely  wants  competentemployee to work in their company.  That’s way every big company certainly has adepartment  named  Human  Resource  Developemnt  (HRD).  Human  ResourceDevelopment is the framework for helping employees to develop their personal andorganizational  skills,  knowledge,  and abilities.  The focus of all  aspects of HumanResource Development  is  on developing the most  superior  workforce so that  theorganization and individual  employees  can accomplish their  work goals  in givingservice to customers.  PT. TELKOM is one of many companies in Indonesia whichhas Human Resource Development to manage its employees.  The writer conductedJob  Orientation  in  PT.  TELKOM to  learn  all  activities  in  Human  ResourceDevelopment and to feel the condition and the atmosphere in it.The writer chose PT. TELKOM Malang because of some reasons. The mainreason is the writer thought that PT. TELKOM Malang is one of the big companies inMalang,  so  it  has  a  lot  of  employees,  and  there  will  be  a  Human  ResourceDevelopment department which is smart, strong, professional and competent and canhandle the employees  excellently because actually the writer  wants to learn aboutHuman Resource Development and hope to become a manager of human resourcedevelopment as one of his expectations after he passes his study.The writer conducted Job Orientation since 19 January 2009 to 6 February2009. The writer  was placed in HR-Reppresentative department  in PT.  TELKOMKandatel Malang. The writer had some responsibilities to support the job of HRD as astaff.Because of the activities the writer knows a kind of atmosphere of job fieldand knows some activities that usually are done by HR-Representative, including theactivities which relate with employees. The writer also knows about implementationof Appraisal Performance and Competence Development in PT. TELKOM althoughit is not too complete.Actually the writer  got precious job position in HR-Representative of PT.TELKOM which  is  a  Human  Resource  Development  Department  there,  and thewriter  got  some  experiences  and  knowledge  about  HRD.  Hopefully,  the  writerexpects that the writer will be a part of Human Resource Development. Keywords: PT. TELKOM Kandatel Malang, staff Human Resource Developmaent